Análise e aplicações biotecnologias de proteínas ligantes à quitina de sementes de cajueiro anão-precoce (anacardium occidentale var. Nanum) - Aragão, Jedson Antonio de Souza (2015)
The cashew (Anacardium occidentale L.) is a plant native to Brazil with high market value. This contributes to the generation of thousands of direct and indirect jobs, especially in the Northeast, in the dry season. Breeding program has been selecting the best cashew cultivars adapted to semi-arid environment in order to put it in an increasingly competitive market. Among the types of seed proteins have several reservation function, structural or metabolic. Furthermore, plants are arranged in an array of defense mechanisms against pathogen attack. One of the most studied defense response with respect to the expression of pathogenesis related proteins which are included in the group of chitinases. The enzyme chitinase (EC 3.2.1.14) hydrolyse the polymer chitin to N-acetyl glucosamine by either endo or exo cleavage of β connection (1-4). The molecular profiles of responses in plants transcriptional level have been shown to be crucial for the establishment of a set of defense mechanisms against invading pathogens. Using bioinformatics tools were identified in the transcriptome cashew CCP076 ten contigs having high degree of similarity with chitinases, endoquitinases and chitinase-like the GH18 family and GH 19 of Ricinus communis, Cicer arietinum, Mangifera indica, Citrus sinensis, Euonymus europaeus , Vitis vinifera, Aegilops tauschii and Hevea brasiliensis. The enzyme assays of chestnut chitinase protein confirmed the presence in their proteome. Also revealed a great catalytic activity at pH 5. A protein profile with chitin-binding site was also found. Of these, it is demonstrated great potential in biotechnological chitinase from CCP76 cashew nuts.